DYNAMICS OF THE FLUX JUMPS IN SUPERCONDUCTORS - Taylanov, Nizom; Turakulov, Botir (Физико-технологического образование, 2022)
In this work, the spatial and temporal distributions of small thermal and electromagnetic perturbations in a plane semi-infinite superconducting sample are studied. Based on a system of equations for temperature, magnetic induction, and vortex motion, a dispersion relation was obtained that determines the growth (or decay) increment of small perturbations. It was shown that, under certain conditions, depending on the values of the parameters of the system, flux jumps of the magnetic flux are observed